THE EFFECT OF BILINGUAL EDUCATION ON LITERACY RATES IN MULTILINGUAL SOCIETIES - Sultanova Shohistaxon Shavkatovna (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Annotation: This paper examines the relationship between bilingual education and literacy rates in multilingual societies, with a focus on how mother-tongue-based learning combined with a second language can improve literacy outcomes. Drawing on evidence from both developed and developing countries, it explores how bilingual programs address challenges such as high dropout rates, low reading proficiency, and language barriers in education. The study highlights how culturally and linguistically relevant teaching methods enhance reading and writing skills, promote student engagement, and contribute to long-term academic success.